PEMBERIAN DUA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN AWAL RUMPUT RAJA (Penisetum Purpuphoides) - Kolway, Yoap; Joris, Lily; Eoh, Marna (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
The purpose of this study was to determine the effect of two types of manure on the early growth of king grass (pennisetum putpuphoides). The tools used in this study were scales, tape measure, stationery, writing tools, polybags, machetes, hoe, scope and raffia rope. The materials used in the research were king grass seeds in the form of cuttings of two segments and three nodes, manure of cow manure and manure of goat manure. The method used in this research is the experimental method. This study used a completely randomized design (CRD) with three (3) treatments, namely: PO (without the use of manure). P1 (cow manure) and P2 (goat manure). Each treatment was repeated four (4) times. Variables observed in this study include: number of shoots, leaf length, leaf width, plant height. The results showed that the number of shoots in the initial growth of king grass in weeks 1-3 was the same, but in week 4 the number of shoots in P1 and P2 was different from P0. Leaf length for each treatment was different from week 1 where treatments P1 and P2 showed differences from P0. Leaf widths differed between treatments from week 1 – 4 where treatments P1 and P2 differed from P0. Plant height at weeks 1 and 2 showed that the P1 and P2 treatments were different from P0, but at weeks 3 and 4 the P2 treatments were different from the P1 and P0 treatments.